Modeling the adoption of identification standards in US hospitals: A systems dynamics approach (2011)
This paper summarizes the findings related to the current modeling efforts of identification standards adoption using a system dynamics SD modeling approach. A literature review on technology adoption provides the basis for the decision to utilize the SD approach. The SD model builds off previous findings related to the factors affecting identification standards adoption and relates the specific elements to the adoption rate. These elements are introduced in the model using a causal loop diagram, and then a stock flow model is constructed based on the Bass diffusion model. The model is used to simulate the behavior of the hospital population over time and to observe the impact of the external and internal diffusion coefficients in the adoption rate. Initial efforts focus on the provider perspective but other healthcare supply chain members can be introduced in the model due to its flexibility. The SD model allows for the analysis and design of policies to move the adoption process forward. The preliminary findings are discussed along with the implications on subsequent modeling efforts.